Oftalmopathies in 574 dogs of the breed Shih tzus attended at the Veterinary Hospital: retrospective study - Marchini, Larissa [UNESP]; Fachini, Francimery Aparecida [UNESP]; Rabelo, Isabela Peixoto [UNESP]; Moras, Paola Castro [UNESP] (FapUNIFESP (SciELO), 2024)
Brachycephalic breeds, including Shih Tzus, are predisposed to developing ophthalmic conditions due to facial conformation. This study investigated the primary ophthalmic diseases in Shih Tzus treated at the Governador Laudo Natel's Veterinary Hospital of São Paulo State University Júlio de Mesquita Filho, Jaboticabal-São Paulo, Brazil, between 2014 and 2022. We selected 574 cases, totaling 1,724 diagnoses. Regarding sex, 50% (287/574) were female, and 50% (287/574) were male. Anatomically, diagnoses in group 1 (lacrimal system, eyelids, and adnexa) were the most common, comprising 55% (945/1,724), followed by group 2 (anterior segment) at 40% (683/1,724), group 4 (eyeball) at 4% (73/1,724), and group 3 (posterior segment) at 1% (23/1,724). The mean age at diagnosis was 5.2 years. Adult dogs were the most represented age group at 55% (317/574), followed by young dogs at 25% (145/574) and elderly dogs at 20% (112/574). Elderly dogs had more diagnoses of glaucoma and cataracts compared to young and adult dogs. In young dogs, the most diagnosed conditions were ulcerative keratitis and distichiasis, while in adults and elderly dogs, the predominant conditions were keratoconjunctivitis sicca and ulcerative keratitis.
Oftalmopatias em 574 cães da raça Shih tzu atendidos em um Hospital Veterinário: estudo retrospectivo
Keywords: brachycephalic breed; cataract; distichiasis; entropion; keratoconjunctivitis sicca; ulcerative keratitis